(untitled) (International Journal of Geoscience, Engineering and Technology, 2024)
The study addresses the impact of adding colored pigments on the compressive strength of self-leveling mortar. This simplified application solution is carried out using a concrete mixer truck and hose, reducing the need for labor and accelerating the construction process. Through resistance tests and color analysis, five mortar mixes with different types and proportions of pigments were investigated. The results indicate that the amount and type of pigment can influence the strength and stability of the mortar, with inorganic pigments contributing to the formation of voids and, consequently, to the reduction of strength. Furthermore, the color analysis revealed that the pigments provided uniform and stable shades, essential for aesthetic floor and wall covering applications. Additional investigations should be carried out to deepen the understanding of the influence of pigments on the durability and performance of mortar in different environmental conditions.